Strengthening Students' Religious Character Through Basic Darul Arqam Training Using the MICAR Model Approach: A Case Study at Muhammadiyah University of Bandung - Amriani Amriani; Amril Amril; Mehmet Cuma Tahiroglu; Abdul Kadir; Andi Achmad Syam (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
The development of religious character is a fundamental component of Muhammadiyah higher education. The Basic Darul Arqam Training (DAD) serves as a strategic leadership development tool for instilling Islamic values, yet its effectiveness is highly dependent on the pedagogical approach employed. This study aims to describe and analyze the process of strengthening students’ religious character through the application of the MICAR Model (Motivation, Interaction, Collaboration, Attention, Reflection) in DAD training at Muhammadiyah University of Bandung. The research method employs a qualitative approach with a case study design. Data collection techniques included participant observation, in-depth interviews with participants and instructors, document analysis, and participants’ written reflections. Data analysis was conducted using the Miles and Huberman technique: data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the MICAR Model is capable of strengthening students’ religious character through increased spiritual motivation, intensive religious interaction among participants, collaboration in worship activities and Islamic discussions, deep attention to the values of Muhammadiyah teachings, and spiritual reflection that encourages attitudinal change. These findings confirm that the integration of MICAR into DAD training can serve as an effective and transformative strategy in the formation of students’ religious character.